DISPARITY ON CUMMULATION CASES OF TORT AND BREACH OF CONTRACT - Zakki Adlhiyati; itok dwi kurniawan; muhammad rustamaji; Ismawati septiningsih (Sekolah Tinggi Pariwisata Mataram, 2022)
The discussion on the differentiation between breach of contract and tort has been prevail in a long time. In addition, there is judge’s disparity on the breach of contract and tort cumulation cases. Three cumulation dicisions were anallysed to understand the legal reasoning of the judges. Legal as well as conceptual approach used to reveal the strong relationship between breach of contract and tort in actual cases. Despite the different nature of the cases, the principle of tort existed on the breach of contract. However, the disparities of the awards occured on the actual cases. Firstly, judge consider that the cumulation is formally invalid hence the claim is unacceptable. Finally, on others cases the former reason is put aside and the judges acknowledge the strong relation between breach of contract and tort. Furthermore, systematical legal reasoning is used to grant the claims. With regard to the fairness, judge as the law enforcer need to give reasonable decision with their intellectuality.